2020
DOI: 10.21873/invivo.11900
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Treatment Strategies for the Recurrent Hepatocellular Carcinomas After Radical Resection

Abstract: Background/Aim: The high rate of recurrence and repetitive features of hepatocellular carcinoma (HCC) require specific treatment strategies. This study aimed to evaluate the long-term outcomes of recurrent HCC focusing on clinicopathological factors. Patients and Methods: A total of 104 patients who were treated with re-hepatectomy, radiofrequency ablation (RFA) or transcatheter arterial chemoembolization for recurrent HCC were analyzed. Postrecurrent prognoses were compared between each treatment group based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The study selection process is shown in Figure 1. Ultimately, 18 studies (1 RCT, 3 propensity score matching-non RCTs [PSM-NRCTs], 14 NRCTs) compared LR with RFA for RHCC were included in our meta-analysis [10][11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The included studies evaluated a total of 1991 patients with recurrence of HCC; of these, 862 patients underwent LR, and 1129 patients underwent RFA.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study selection process is shown in Figure 1. Ultimately, 18 studies (1 RCT, 3 propensity score matching-non RCTs [PSM-NRCTs], 14 NRCTs) compared LR with RFA for RHCC were included in our meta-analysis [10][11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The included studies evaluated a total of 1991 patients with recurrence of HCC; of these, 862 patients underwent LR, and 1129 patients underwent RFA.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The pooled OS was compared based on 16 studies which incorporated 1902 patients (817 patients for LR, 1085 patients for RFA) [10][11][12][13][24][25][26][27][28][30][31][32][33][34][35][36]. The pooled HR for OS demonstrated that LR had significantly better OS than RFA in recurrent HCC (HR, 0.81; 95% CI, 0.68-0.95; p < .001; I 2 ¼ 0.0%) (Figure 2(A)).…”
Section: Overall Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen total studies, incorporating 2597 total patients (1203 in the RHR group versus 1394 in the RFA group), were deemed eligible for inclusion in the final data analysis ( Figure 1 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The majority of studies originated from East Asia (nine studies from China, three from Japan, one from Singapore, two from Taiwan and one from Korea), while one study was an international multicenter study.…”
Section: Resultsmentioning
confidence: 99%